Oxytocin receptor ligand binding in embryonic tissue and postnatal brain development of the C57BL/6J mouse - Hammock, Elizabeth; Levitt, Pat (Frontiers in Behavioral Neuroscience, 2013)
Oxytocin (OXT) has drawn increasing attention as a developmentally relevant neuropeptide given its role in the brain regulation of social behavior. It has been suggested that OXT plays an important role in the infant brain during caregiver attachment in nurturing familial contexts, but there is incomplete experimental evidence. Mouse models of OXT system genes have been particularly informative for the role of the OXT system in social behavior, however, the developing brain areas that could respond to ligand activation of the OXT receptor (OXTR) have yet to be identified in this species. Here we report new data revealing dynamic ligand-binding distribution of OXTR in the developing mouse brain. Using male and female C57BL/6J mice at postnatal days (P) 0, 7, 14, 21, 35, and 60 we quantified OXTR ligand binding in several brain areas which changed across development. Further, we describe OXTR ligand binding in select tissues of the near-term whole embryo at E18.5. Together, these data aid in the interpretation of findings in mouse models of the OXT system and generate new testable hypotheses for developmental roles for OXT in mammalian systems. We discuss our findings in the context of developmental disorders (including autism), attachment biology, and infant physiological regulation.